Prabhakar fractional derivative model of sodium alginate (C6H9NaO7) for accelerated plate motions - Khan, Ilyas (Frontiers in Energy Research, 2022)
Sodium-Alginate (C6H9NAO7) is taken here as an example of Casson fluid, has various practical applications, for instance, in bio-engineering operations, metallurgy, food processing, and drilling operations. The current study investigates thermal transport of Prabhakar fractional derivative model of sodium-alginate (C6H9NAO7) with constant heating condition. Since, the classical PDEs are incapable of analyzing and investigating the physical impact of flow variables with memory effects, therefore, fractional derivative model is developed instead of classical one. The non-dimensional governing equations are transformed into a fractional model and solved using the Laplace transformation (L.T) technique. The effects and behavior of significant physical parameters and fractional order parameter are studied graphically and discussed. As a consequence, it is found that as fractional limitations are increased, the thermal and momentum profiles drop. In addition, the momentum profile in case of quadratic translation (variable acceleration), shows higher magnitude compare to the case of linear translation (constantly accelerated plate).